The Influence of Human Resources in Successfully Improving the Quality of Employee Performance (Systematic Literature Review) - Sugiyono; Zahara Tussoleha Rony (Dinasti Publisher, 2024)
Competence is basically a dimension of abilities, skills, and attitudes required of a person to be able to meet the demands of the position in general and can be considered as a requirement for a person to carry out his work professionally. Human resources have a very important role in an organization. Without human resources or lack of quality of human resources, companies or organizations will be difficult to run and operate properly. One of the things that companies can do in managing and maintaining human resources is to pay attention to the quality of employee performance. The purpose of SLR is to analyze the Influence of Human Resources in the Success of Improving the Quality of Employee Performance. The results of this literature review study show that the company's success rate is the performance of its employees. Every employee certainly wants to be one part of the company's success, Performance is a real effort given by each individual or group in accordance with his role to the company. An employee who has high and good performance can support the achievement of goals and objectives set by the company